Changing Trends in the Baby Boomer Travel Market: Importance of Memorable Experiences. Issue 4 (19th May 2017) - Patterson, Ian; Sie, Lintje; Balderas-Cejudo, Adela; Rivera-Hernaez, Olga
Abstract: Globally, the number of baby boomers who are age 60 years and over are expected to more than double, from 841 million people in 2013 to more than 2 billion in 2050. In recent years, boomers have demonstrated that they are willing participants in new and memorable experiences where they can learn and broaden their minds through travel to new locations and to learn more about different cultures through a variety of first-hand experiences. As a result, the numbers of baby boomer travelers over 60 years of age have grown substantially from 593 million international travelers in 1999, which has been forecast to exceed 2 billion trips per annum by 2050. The hotel and resort industry needs to respond to their changing needs, and allow guests to achieve memorable experiences in exotic and different destinations as well as through the provision of hotel design that is inextricably linked to the place they are visiting. This article outlines the changing sociodemographic trends of baby boomers, examines their need for different hotel and resort experiences in an expanding market place, and concludes with a discussion of key marketing considerations.